Intelligent Garbage Classifier - Salmador, Alvaro; Pérez Cid, Javier; Rodríguez Novelle, Ignacio (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
IGC (Intelligent Garbage Classifier) is a system for visual classification and separation of solid waste products. Currently, an important part of the separation effort is based on manual work, from household separation to industrial waste management. Taking advantage of the technologies currently available, a system has been built that can analyze images from a camera and control a robot arm and conveyor belt to automatically separate different kinds of waste.
Keywords: classification; objects; recycling; robotics; waste management; computer vision; IJIMAI